2006
DOI: 10.3766/jaaa.17.8.2
|View full text |Cite
|
Sign up to set email alerts
|

The Need for and Development of an Adaptive Listening and Communication Enhancement (LACE™) Program

Abstract: Auditory training has long been advocated to enhance communication but has never been time or cost-effective. This article describes the concepts underlying the development of a home-based, interactive adaptive computer program designed to engage the adult hearing-impaired listener in the hearing-aid-fitting process, provide listening strategies, build confidence, and address cognitive changes characteristic of the aging process. An investigation using a between-group, within-subject design with pre- and post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
242
2
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 226 publications
(257 citation statements)
references
References 56 publications
8
242
2
5
Order By: Relevance
“…It is believed that by enhancing the speech signal, more resources are made available for use in higher-level auditory processing. Auditory training has been shown to be successful for children with language learning disorders [86][87], for improving satisfaction and performance of adult hearing aid users [86][87][88], and for enhancing the memory of older adults [89]. An accumulating body of literature shows that auditory training has the potential to change neural function, as demonstrated by changes in electrophysiological metrics such as increased P300 amplitude and decreased latency to speech signals [87,90] and changes in the amplitude and latencies of the N1-P2 complex [91][92].…”
Section: Rehabilitationmentioning
confidence: 99%
“…It is believed that by enhancing the speech signal, more resources are made available for use in higher-level auditory processing. Auditory training has been shown to be successful for children with language learning disorders [86][87], for improving satisfaction and performance of adult hearing aid users [86][87][88], and for enhancing the memory of older adults [89]. An accumulating body of literature shows that auditory training has the potential to change neural function, as demonstrated by changes in electrophysiological metrics such as increased P300 amplitude and decreased latency to speech signals [87,90] and changes in the amplitude and latencies of the N1-P2 complex [91][92].…”
Section: Rehabilitationmentioning
confidence: 99%
“…Further study with more sensitive tests is needed to evaluate the impact of syllable identification training on sentence processing. Recently, more complex adaptive training sequences have shown efficacy in improving sentence test scores [66].…”
Section: Effect Of Training On Sentence Processingmentioning
confidence: 99%
“…that auditory training involving the practice of a variety of listening situations as part of an auditory rehabilitation intervention programme (with home practice tasks as well) will lead to enhanced speech recognition and better perception in various listening situations. Similarly, a study conducted by Sweetow and Sabes [28] developed a home-based computerised listening and communication enhancement programme for hearing impaired adults which showed that participants who used the training programme improved significantly in terms of both subjective and objective measures.…”
Section: Discussionmentioning
confidence: 97%